SAMPANG REGENCY GOVERNMENT'S EFFORTS IN ACCELERATING HALAL CERTIFICATION OF UMKM MAQASHID SYARIAH PERSPECTIVE - Musadad, Ahmad (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
Sampang Regency is one of the cities located on Madura Island, East Java Province. In 2020, there were 30,830 thousand UMKM, which were divided into 30,618 micro enterprises, 178 small enterprises and 34 medium enterprises according to those recorded in the Cooperatives, Micro Enterprises and Manpower Office in Sampang Regency (Salam and Makhtum 2022) . Sampang Regency, which is predominantly Muslim, of course needs halal certification. One way to create benefits in everyday life is to adopt a halal lifestyle. To achieve benefits through a halal lifestyle, a guarantee is needed that covers all the needs of a halal lifestyle. This assurance is implemented through a halal certification system. This study aims to find out how the efforts of the Sampang Regency government in accelerating the halal certification of UMKM from a sharia maqashid perspective. The applied research method is qualitative research method, where the data collection process is carried out through site survey techniques for sampling. Data collection was conducted using interviews as a tool to obtain information on the acceleration of halal certification implementation in Sampang Regency.